Letter - Halifax, Edward Frederick Lindley Wood, Earl of, 1881-1959
013-0057-001 Foreign Office, S.W.1. 28th November, 1940. Dear Sir On the 15th November you wrote to me about the the two Spanish Republican Leaders Largo Caballero and Manuel Cordero. I am afraid that it is no easier to intervene successfully with the Spanish authorities on behalf of political prisoners than it was some months ago. But I will immediately ask your Ambassador in Spain whether there are any steps he can take on Largo Caballero'e behalf and I am sure that, if anything can be done, the Ambassador will do his best. As regards Manuel Cordero, his case had already been brought to my notice by the Lord Privy Seal and instructions have been sent to our Ambassador in Lisbon to take any steps he can to assist. Y. sincerely Halifax H.V. Tewson, Esq. 292/946/13/57